Pembekalan dan Pendampingan Motivasi Penerapan Psikologi Belajar Dalam Meningkatkan Kwalitas Proses Pembelajaran Pada Guru Pendidikan Agama Kristen Di Solo - Sri Wening; Budi Widianto; Ayub Widhi Rumekso (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Teachers are people who have a big role in the continuity of an optimal and quality learning process, because student activity and the development of student potential cannot be separated from the teacher’s ability to approach learning in the ongoing learning process. The emergence of problems in the learning process can originate from the limitation of teachers and students which have an impact on learning process that is not conducive. The application of learning Psikologi in the learning prosces is a way for teachers to overcome learning problems and improve the quality of learning. Teacher abilities in approaching and mentoring require refresing as a strategy to refresh and inrease teaher motivation in designing and realizing improvements in the quality of the learning process. This community activity aims to provide motivational traning and assistance for teachers in an effort to provide additional knowledge and insight tp motivate teachers to answe every learning problem and provide input in finding student approach strategi to achieve improved learning quality. This activity received a positive response and helped teachers to increase their roles and in realizing improvements in the quality of the learning process